English-French Macaronic Songs in Canada — A Research Note And Query - Posen, I. Sheldon (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1992)
A macaronic song or narrative is one that intersperses two or more languages, with that of the narrative voice predominating. At least five English- French or French-English macaronic songs have circulated traditionally in Canada. Francophone and anglophone scholars rationalize their origin in bilingual dysfunction: they see in them a legacy of francophone Quebec and Acadian immigrants to New England who returned to Canada with songs half-remembered in two languages. My own opinion is that these songs comprise a bona fide song genre that originated as and is meant to be macaronic. I speculate that they might come out of a popular music tradition aimed at a relatively small, rather urbane, bilingual audience in Montreal or Quebec City.